Optimisasi Energi Melalui Pelatihan Mekanisasi Sistem Kontrol Mobil Listrik: Sebuah Pendekatan PKM - Amiruddin; Hidayat, Akmal; Iris Sumariyanto; Muhammad Hasim S; Muhammad Haristo Rahman (Jurusan Teknik Informatika dan Komputer, 2023)
The increasing population growth and demand for transportation energy in Indonesia, particularly from fossil fuel-powered vehicles, highlight the urgency of adopting environmentally friendly technologies. The government's focus on electric vehicles is promising, but it requires competent human resources support. The Community Service Program (PKM) titled